Sustainability of an Enhanced Recovery After Surgery initiative for elective colorectal resections in a community hospital - Norman, Alexander (Can J Surg, 2020)
BACKGROUND: In March 2016, an Enhanced Recovery After Surgery (ERAS) initiative was implemented for all elective colorectal resections at an urban hospital in St. John’s, Newfoundland and Labrador, Canada. An ERAS coordinator supervised and enforced guideline compliance for 6 months. The aim of this study was to evaluate the sustainability of the ERAS program after supervision of guideline compliance was eliminated. METHODS: Patient outcomes and guideline compliance were compared between surgeries performed under standard practice (April 2014 to March 2015) and those performed during and after the implementation of the ERAS initiative (March 2016 to August 2016 was the implementation phase and September 2016 to February 2017 was the sustainability phase). RESULTS: Hospital length of stay decreased from 7.26 days at baseline to 5.44 days during the implementation phase of the ERAS program (p < 0.001). There was no significant difference between length of stay at baseline and during the 6-month sustainability phase of the ERAS program (7.10 d). There were no significant differences in rates of readmission or mortality during and after implementation. Rate of ileus decreased significantly from 13.8% during the implementation phase to 4.6% during the sustainability phase (p = 0.036). Total guideline compliance increased from 52.2% at baseline to 80.7% during the implementation phase (p < 0.001), and decreased to 74.7% during the sustainability phase (p < 0.001). Adherence to postoperative guidelines regressed: 79.2% in the implementation phase and 68.6% in the sustainability phase (p < 0.001). CONCLUSION: Hospital length of stay decreased when the ERAS program was implemented and the ERAS coordinator was present on the surgical ward. Methods for sustaining guideline implementation are vital to the success of similar programs in the future.